Effects of removing vitamin and mineral premixes on growth performance and carcass measurements in finishing pigs - J S Park; Terry L Gugle; C L Jones; C W Starkey; D J Lee; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2000)
Two hundreds sixteen pigs were used to determine the effects of deleting vitamin and mineral premixes on growth performance, carcass characteristics, and integrity of vertebrae in finishing pigs housed in large groups with extreme variation in BW. No negative effects on ADG, ADFI, F/G, carcass characteristics, or integrity of vertebrae occurred when the vitamin and mineral premix was deleted.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Finishing pigs; Vitamins; Minerals